Task shifting of intravitreal injections from physicians to nurses: a qualitative study - Stine Bolme; Dordi Austeng; Kari Hanne Gjeilo (BMC, 2021)
Abstract Background Intravitreal injections of anti-vascular endothelial growth factor are high-volume procedures and represent a considerable workload on ophthalmology departments. Several departments have tried to meet this increase by shifting the task to nurses. To maintain high-quality patient care, we developed a training program for nurses that certifies them to administer injections. This qualitative study aimed to evaluate whether the nurses were confident and in control after participating in the training program and whether they were satisfied with the training and the new task. Methods Between 2014 and 2018, 12 registered nurses were trained in a tertiary hospital in central Norway. All the nurses were interviewed, either individually (n = 7) or in a group (n = 5). We analysed the interviews using Graneheim and Lundman's qualitative content analysis. Results Eight subthemes were clustered within four main themes: 1) procedure and challenges, 2) motivation, 3) cooperation and confidence, and 4) evaluation. The nurses felt confident and in control when administering injections but experienced moments of insecurity. The new task gave the nurses a sense of achievement, and they highlighted improvement of patients' lives as positive. A greater level of responsibility gave the nurses pride in their profession. They had suggestions that could improve training efficiency but were overall satisfied with the training program. Conclusions Our study showed that the nurses were satisfied with the training and that learning a new task led to higher self-esteem and increased respect from patients and colleagues. Suggestions to improve the training were identified; these should be considered before implementation by other departments.